Upper crustal structure beneath the Qin-Hang and Wuyishan metallogenic belts in Southeast China as revealed by a joint active and passive seismic experiment. Issue 1 (24th August 2022) - Zheng, Mengjie; Xu, Tao; Lü, Qingtian; Lin, Jiyan; Huang, Minfu; Bai, Zhiming; Deng, Yangfan; Zhang, Yongqian; Badal, José
SUMMARY: Southeast China is one of the most important polymetallic metallogenic provinces in the world. However, distinct differences in the type and origin of the mineral deposits are present between the major metallogenic belts in this province. To deepen our knowledge of this regional metallogenic setting, investigate the factors controlling its metallogenic differences and explore the feasibility of active and passive seismic imaging, we performed a multibatch seismic experiment using active and passive sources with the help of 437 short-period seismographs deployed across the Qin-Hang and Wuyishan metallogenic belts in Southeast China. We resolved the S -wave velocity structure beneath the profile using ambient noise tomography and derived a Vp/Vs model by combining with a published P -wave model. A good correlation between the obtained seismic velocity models and geological observations is observed. The Proterozoic volcanic-sedimentary rock series and the Fuzhou-Yongfeng sedimentary basin are identified by low P - and S -wave velocities, high Vp/Vs ratios and low S -wave velocity perturbations. Within the core of the Wuyishan Metallogenic Belt, several narrow, elongated and low seismic velocity anomalies are considered to be signs of the nearby fault zones, and these anomalies provide reference information on the extension and pattern of these faults at depth. Combined with the geological and mineralogical evidence, we propose that theses faults function as ore-guiding structures and facilitate the formation of regionally representative mineral species and metal assemblages.